Makalah: Ratifikasi Hukum Internasional dalam Penguatan Kebijakan Nasional Mengenai Preservasi Peninggalan Sejarah Nasional - Arsetyo, Yulio Iqbal Cahyo (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
"Indonesia is a country with a rich culture and historical heritage. However, this wealth is like a double-edged sword. On one hand, historical relics offer great opportunities for tourism, but on the other hand, conservation challenges such as funding and the theft of historical artifacts must be addressed seriously. To tackle this issue, Indonesia needs to make joint efforts with the international community through the ratification of international laws that can strengthen national policies related to the preservation of historical heritage. This research aims to analyze how international law can reinforce national policies in the conservation of Indonesia's national historical heritage. This research is qualitative with a normative juridical method. The results of the study indicate that the ratification of international legal instruments not only enhances international recognition but also brings support and protection guarantees for historical heritage objects at the international level."